2004
DOI: 10.1554/03-597
|View full text |Cite
|
Sign up to set email alerts
|

Inbreeding in the Seychelles Warbler: Environment-Dependent Maternal Effects

Abstract: Abstract. The deleterious effects of inbreeding can be substantial in wild populations and mechanisms to avoid such matings have evolved in many organisms. In situations where social mate choice is restricted, extrapair paternity may be a strategy used by females to avoid inbreeding and increase offspring heterozygosity. In the cooperatively breeding Seychelles warbler, Acrocephalus sechellensis, neither social nor extrapair mate choice was used to avoid inbreeding facultatively, and close inbreeding occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(98 citation statements)
references
References 85 publications
6
87
5
Order By: Relevance
“…Pairwise genetic relatedness ( R ) was estimated based on 30 microsatellite loci (Richardson et al., ; Spurgin et al., ) using the Queller and Goodnight () estimation implemented in the r ‐package “ related ” v0.8 (Pew, Muir, Wang, & Frasier, ). A previous study using these microsatellite loci in the Seychelles warbler has confirmed that relatedness for known parent–offspring pairs does not differ from R = 0.5 (Richardson, Komdeur, & Burke, ). To determine whether dispersers that joined another territory as non‐natal subordinates ( n = 3 males, n = 20 females) obtained parentage as subordinates, we assigned parentage for all offspring that were produced in that territory during a focal subordinate's tenure using masterbayes 2.52 (Hadfield et al., ; Dugdale et al.…”
Section: Methodsmentioning
confidence: 52%
“…Pairwise genetic relatedness ( R ) was estimated based on 30 microsatellite loci (Richardson et al., ; Spurgin et al., ) using the Queller and Goodnight () estimation implemented in the r ‐package “ related ” v0.8 (Pew, Muir, Wang, & Frasier, ). A previous study using these microsatellite loci in the Seychelles warbler has confirmed that relatedness for known parent–offspring pairs does not differ from R = 0.5 (Richardson, Komdeur, & Burke, ). To determine whether dispersers that joined another territory as non‐natal subordinates ( n = 3 males, n = 20 females) obtained parentage as subordinates, we assigned parentage for all offspring that were produced in that territory during a focal subordinate's tenure using masterbayes 2.52 (Hadfield et al., ; Dugdale et al.…”
Section: Methodsmentioning
confidence: 52%
“…, 2008). Furthermore, there is evidence that close inbreeding occurs in this population (Richardson et al. , 2004; Brouwer et al.…”
Section: Introductionmentioning
confidence: 90%
“…Second, we assess if individuals that do disperse from their natal territory avoid related individuals as mates. A previous study on the Seychelles warblers that compared the relatedness of existing pairs with all potential random pairs across the entire population found no evidence for inbreeding avoidance through social or extra‐pair mate choice (Richardson et al. , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the results reported here, most studies have found strong effects of inbreeding as well as interactions with environment at most life history stages (Keller et al 1994, Marr et al 2006, Szulkin and Sheldon 2007). Other studies have shown that inbreeding depression may only be expressed, and therefore interactions observable, when environmental conditions are very adverse (Keller et al 2002, Richardson et al 2004). Weather variables in our study had high relative importance at several stages, but these effects were variable and imprecise.…”
Section: Discussionmentioning
confidence: 99%
“…In song sparrows Melospiza melodia , prolonged periods of rain increased the severity of inbreeding depression for female hatching success (Marr et al 2006), and severe winters decreased overall survival (Keller et al 1994). Similarly, stressful environmental conditions reduced reproductive success of inbred females in the Seychelles warbler Acrocephalus sechellensis (Richardson et al 2004). Environmental influence on inbreeding depression has also been observed in Darwin's finches Geospiza scadens and G. fortis (Keller et al 2002) and great tits Parus major (Szulkin and Sheldon 2007).…”
mentioning
confidence: 99%